Tourists' attitudes toward green product buying behaviors: The role of demographic variables - yeliz Pekersen; Fatma Canöz (Tourism & Management Studies)
Green products do not harm the environment or natural resources and support recycling. Due to tourists having different demographic characteristics, their demands and needs differ, and therefore their thoughts on green products also vary. Therefore, this study focuses on tourists' green product buying behaviours. In this context, the research aims to determine whether tourists' green product buying behaviours differ concerning demographic variables. The survey form prepared for this purpose was applied to 418 tourists visiting Istanbul. As a result of the research, foreign tourists' demographic variables were determined to affect their green product buying behaviours, with factors other than marital status and income level not contributing to tourists' environmental product preferences or their environmental sensitivity. Research has found that single tourists are more sensitive to the environment than married tourists. In addition, economically strong individuals were determined to be willing to pay more money for green products if they had sufficient purchasing power.